Clock towers as the focus of city square: The changing scale of nusretiye clock tower - ALTINTAŞ, MERİÇ; DEMİR, ELİF GELMEZ (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2018)
Tophane, with its historical and cultural heritage, is acknowledged to be one of the most significant districts of Istanbul. Formerly known for its gardens, the district has acquired a different identity after the Ottoman conquest of Istanbul in 1453. Tophane-i Amire, being the imparial armory which was established in the Ottoman period did not only name the region, but also altered the social and cultural profile of the district to a great extent. The region has suffered the great fires of Istanbul and been damaged many times by them, thus the architectural texture it possesses had undergone many changes both due to these disasters as well as political and governmental adjustments of the authority. In time, the growth and continuous territorial expansion of Ottoman dominion necessitated the innovations and advancements in the military along with the construction of additional buildings to the Tophane facilities. Together with the additional buildings, the area had once again acquired a distinct identity where civil and military architectural examples coexist. Following the effects of industrialization seen in the late 19th century, the escalating growth of the city, beginning in the early 20th century, has reached levels that prevent the perception of the integrity among Tophane facilities. After 1950, the starting of customs house constructions and the expropriation policies had changed Tophane beyond all recognition. Being completed in the second half of the 19th century, Nusretiye (Tophane) clock tower is known to be the first clock tower of Istanbul. During the period of its construction, the clock tower had been in the center of the military drill field, defining a circumferential open space by itself. However, due to the expropriation policy of the 1950s, it was taken to another spot where the customs buildings had been located. With this study, a brief examination of Nusretiye clock tower has been conducted to understand its relation to the surroundings with a projection from past to present. To analyze and discuss the established relationships in depth, the Tophane Square and the Tophane Barracks, as architectural representatives of the region and era, were also included in the scope of the study. The study aimed to reveal and present the current conditions of the clock tower, to remark the significance of the surrounding architectural interactions in the perception of an architectural heritage and to discuss the effects of the changes made to the Tophane district.
Keywords: Tophane; Nusretiye Clock Tower; Istanbul; Architecture; Expropriation; Tophane Barracks; City Square